FORMULASI DAN UJI ANTIOKSIDAN EKSTRAK ETANOL DAUN BINAHONG (Anredera Cordifolia) SEBAGAI GEL PELEMBAP - Ginting, Ernawaty; nadia, syarifah; Nurul Karima; rossela; Ovalina Sylvia Br Ginting (Indonesian Journal of Pharmaceutical and Clinical Research, 2024)
Dry skin is often caused by air pollution and sun exposure. Binahong leaves (Anredera Cordifolia) contain flavonoids that can keep the skin moisturized. The gel formulation of binahong leaf extract was chosen because it has good penetration, making it an effective solution for dry skin.This study began by macerating the simplicia of binahong leaves (Anredera Cordifolia) with ethanol p.a (1:10), then formulated into gel preparations with concentrations of 2.5%, 3% and 3.5% with CMC, TEA, nipagin, glycerin and propylene glycol as gel preparation ingredients. Then the physical quality of the preparation was checked which included organoleptic test, pH test, homogeneity test, stability test, dispersion test, adhesion test, irritation test, liking test and viscosity test. In addition, moisture tests and antioxidant tests were carried out using the DPPH method. The gel formulation made has met the physical quality requirements of the preparation, namely all preparations are homogeneous, stable and do not irritate the skin. The pH value is 4.5-4.8, the spread power is 5.5-6.8 cm, the adhesion value is 15-24 seconds and the viscosity value is 12,400-22,299 m.Pas. The amount of antioxidants in formulation 3 was 84.61 mcg/mL ± 0.05 with the strong category and the recovery percentage was 66.94% with a very humid scale. The amount of antioxidants in formulation 2 was 118.56 mcg/mL ± 0.00 with the medium category and the percent recovery was 54.39% with a humid scale. The number of antioxidants in formulation 1 was 163.98 mcg/mL ± 5.71 with the weak category and the recovery percentage was 44.50% with the dry scale. Formulation 3 with a concentration of 3.5% has the highest antioxidants and recovery.